Normative single joint isometric hamstring strength scores from professional soccer players during preseason - Ripley, N. J.; Fahey, J. T.; Comfort, P.; McMahon, J. J.; Jones, P. A.; Bramah, C. (The Journal of Strength and Conditioning Research, 2025)
Monitoring changes in isometric force production from the hamstrings has become increasingly common in team sports. With an increase in force plate availability in soccer, isometric hamstring assessments have become popular, yet normative benchmarks do not currently exist. The purpose of this study was to provide normative force production benchmarks for professional soccer players obtained during isometric hamstring assessments. One hundred forty-two senior professional men's soccer players (age, 24.56 ± 5.09 years; height, 183.63 ± 5.84 cm; mass, 82.12 ± 8.35 kg) performed 2 isometric assessments with 30° and 90° of hip flexion and similar knee joint angles. Mean and standard deviation were determined across 3 trials, differences between soccer positions (goalkeeper, defender, midfielder, and strikers) and differences between limbs were determined through one-way ANOVA. p value was set at <0.05, and effect size was calculated using Cohens d. Benchmarks were developed using T-scores. Trivial-moderate positional differences (d = 0.09-0.95) were observed for absolute peak force, whereas only trivial positional differences (d = 0.00-0.01) were observed for relative peak force (i.e., peak force/body mass). Trivial between limb differences (d = 0.12-0.13) were observed for assessment performed at 90°; however, small differences were observed in the 30° test (d = 0.27-0.29). Benchmark values are provided for relative peak force due to no meaningful difference between positions. Practitioners could use the normative benchmarks provided to determine training needs and establish specific goals. The isometric hamstring assessment positioned at 30° of knee and hip flexion may be more sensitive to determine interlimb differences.